2020
DOI: 10.1002/ps.5980
|View full text |Cite
|
Sign up to set email alerts
|

Introgressive hybridization between two non‐native apple snails in China: widespread hybridization and homogenization in egg morphology

Abstract: BACKGROUND: Apple snails from the genus Pomacea have spread widely in paddy fields and other wetlands of southern China since their introduction in the 1980s. Pomacea spp. are commonly identified using mitochondrial COI sequences. However, sequencing the nuclear elongation factor 1-alpha (EF1⊍) gene revealed genetic introgression between field populations of P. canaliculata and P. maculata, which produce surviving hybrids in laboratory crossbreeding experiments. RESULTS: In this study, we sequenced 1054 EF1⊍ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Individuals with inconsistent identification based on the two genes were hybrids. We genotyped the nuclear EF1α gene for each snail collected from Hong Kong and diagnosed as P. canaliculata or P. maculata using the primer‐specific‐multiplex PCR described by Yang et al (2020). Although a previous study based on the EF1α gene indicated incomplete lineage sorting between P. occulta and P. canaliculata and P. maculata (Yang et al, 2019), we also genotyped the EF1α gene of the snails with a COI type of P. occulta to check the hybridization patterns among these species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals with inconsistent identification based on the two genes were hybrids. We genotyped the nuclear EF1α gene for each snail collected from Hong Kong and diagnosed as P. canaliculata or P. maculata using the primer‐specific‐multiplex PCR described by Yang et al (2020). Although a previous study based on the EF1α gene indicated incomplete lineage sorting between P. occulta and P. canaliculata and P. maculata (Yang et al, 2019), we also genotyped the EF1α gene of the snails with a COI type of P. occulta to check the hybridization patterns among these species.…”
Section: Methodsmentioning
confidence: 99%
“…Although a previous study based on the EF1α gene indicated incomplete lineage sorting between P. occulta and P. canaliculata and P. maculata (Yang et al, 2019), we also genotyped the EF1α gene of the snails with a COI type of P. occulta to check the hybridization patterns among these species. The multiplex PCR assay included two pairs of specific primers (Appendix : Table S1), including EF3Fc/EF3Rc targeting on a 125 bp of canaliculata‐EF1α, and EF1Fm/EF3Rm targeting on a 151 bp of maculata‐EF1α (Yang et al, 2020). We performed PCR in 25 μl solution containing 12.5 μl Premix Taq ™ (Takara), 1 μl each primer (10 mM), 1 μl template DNA, and 7.5 μl ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization is considered to be an important driving force for the adaptive evolution of species [ 22 , 23 ]. Introgression caused by hybridization has been reported in many animals, such as insects [ 24 ], mollusks [ 25 ], mammals [ 26 ], reptiles [ 27 ], amphibians [ 28 ], and fish [ 29 ]. In recent decades, with the frequent occurrence of invasive species introduction events, hybridization opportunities between invasive species and their relatives have increased, and introgressive hybridization progeny may be more invasive, leading to the extinction of local parent groups [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In east and south-east Asia, the apple snails have invaded a wide range from tropical to temperate regions after several introductions(Hayes et al 2008), northern expansion of this species were determined by low temperature during winter(Ito 2002;Syobu et al 2001). Compared with P. canaliculata, P. maculata has poorer tolerance of both cold and desiccation(Yang et al 2020), which was re ected in its distribution in southern, western coastal regions and Florida in US. These ndings on difference in ecophysiological tolerances of the two Pomacea snails, has implications for understanding differential spread potentials in the invasive range.…”
mentioning
confidence: 99%